2057. A Social Network Strategy for HIV Self-Test Kit Distribution through PrEP Program Clients. (15th December 2022) - Doblecki-Lewis, Susanne; Butts, Stefani; Kanamori, Mariano; Johnson, Ariana; Rodriguez, Edda L
Abstract: Background: HIV testing allows care engagement of people living with HIV and PrEP for those who test negative. Social network strategy (SNS) interventions may facilitate distribution of HIV self-test (ST) kits to individuals who do not routinely test for HIV. The University of Miami pre-exposure prophylaxis (PrEP) program offers low-barrier PrEP/HIV prevention services through mobile and static clinics in Miami-Dade County. Current PrEP clients may be ideal distributors of HIV ST kits and PrEP information within their social networks. Methods: Study activities occurred in Miami from November 2021 to March 2022. At PrEP visits, participants (n = 96) were given Ora-Quick oral fluid ST kits for distribution to their social network members. Participant surveys included demographics, feelings of closeness to network members, history of PrEP conversations, and intention for future PrEP conversations. Descriptive statistics included mean and range for continuous variables and frequencies for categorical variables. Network visualizations were constructed using UCINet and NetDraw. Bivariate and regression analysis, conducted in R, assessed the relationship between demographic characteristics of the client and the proportion of network members who discussed PrEP and plan to discuss PrEP in the future between and across networks. Results: A network visualization displays clients (n=96) and their social networks (n=426). Clients and network members were a majority male (84.7%) and of Hispanic/Latinx ethnicity (78.8%). Within and between network analysis indicated that networks differed significantly in reported closeness and frequency of PrEP discussions (F = 2.97; p-value 0.01, F = 17.45; p < 0.03, respectively). Age and average reported closeness of the ego were independently and jointly associated with an increase in the likelihood of future PrEP conversations (estimate = 0.02; p-value < 0.01; estimate = 0.24; p –value < 0.01, respectively). Figure 1: PrEP Discussion & Closeness Node color reflects PrEP discussion and node size reflects client reported closeness Conclusion: We demonstrate the feasibility of disseminating HIV ST kits and PrEP information through SNS. Emotionally closely linked networks, with similar characteristics (i.e., age) may be most effective for this SNS strategy. Disclosures: Susanne Doblecki-Lewis, MD, MSPH, Gilead Sciences: Grant/Research Support.